Molecular phylogeny of Aplosporella abexaminans: a novel species revealing the second report of sexual-asexual connection in Aplosporellaceae (Botryosphaeriales) from India - Verma, Sanjeet Kumar; Yadav, Sanjay; Singh, Raghvendra (Phytotaxa, 2021)
Aplosporella abexaminans, a new sexual morph fungus belongs to family Aplosporellaceae, was discovered on the bark of stem of Murraya koenigii (Rutaceae) and identified by morphological characteristics and analysis of combined ITS and LSU sequence data. This is the second report of a sexual morph with molecular evidence for this genus and the second record of conidiogenesis and chlamydospores associated with the asexual state of this family. It is characterized by its larger ascostromata, locules without ostioles, thinner locule peridium, two to multi-layered, larger asci, surrounded by an additional hyaline sac like structure, larger and hyaline to light olivaceous ascospores, asexual state without conidiomata formation, conidiogenous cells light brown to brown, conidia brown without granular content, smooth and presence of chlamydospores. The sexual morph of Aplosporella abexaminans resembles Bagnisiella and the asexual morph resembles Aplosporella, thus proving the sexual-asexual connection for the second time for this family.